Več kot Geografski informacijski sistem - Bizjak, Igor (Urbani izziv, 2008)
This paper describes a model how to upgrade GIS system to Spatial Decision Support System (SDSS) or Web Spatial Decision Support System (Web SDSS). The purpose of SDSS systems is to help users of the system to make decisions on issues such as finding a suitable location for dumping toxic waste, findig a location for building industrial objects, determinating flooding areas or defining urbanization of a territory. The paper also describes some cases of such systems.
Keywords: geografski informacijski sistemi; odločanje; prostorski podatki; prostorsko planiranje; regionalno planiranje; spatial planning